Analysis of Innovative Gabion Wall Design with Geotextile Reinforcement and Dredged Marine Soil as Backfill Material via PLAXIS 2D - MUHAMMAD AMIRUL HAKIM ABDUL RAHIM; SALINA SANI (Progress in Engineering Application and Technology, 2025)
Gabion retaining walls are very important to stabilize slopes and fight against erosion; using DMS as backfill material is of key importance however, the performance is not as easy as in other materials, because of its low geotechnical properties, high water content and variable composition. Deformation of gabion wall systems DMS are studied using advanced PLAXIS 2D finite element simulations. The testing methodology included a series of extensive laboratory tests for the determination of DMS geotechnical properties and a numerical analysis of six different gabion wall arrangements, with bases from 1 to 5 meters in width. The research is leading to a new and improved form with geotextile reinforcement layers that increase the design's structural integrity. It is found that using the traditional arrangement of gabion wall, in which the horizontal length evolves totally 367.6 meters, the safety factors are smaller than 0.75, this imply that the stability of wall sections are poor in the practice. The best configuration which is encapsulated with geotextile reinforcement provides significant enhancements; also, maximum deformation is decreased to 0.80 meters, and the safety factor is increased to 1.54, and therefore the designed slope stabilizes in the end. These results confirm that it is valid that the strategic use of geotextiles has a marked effect on gabion wall performance for construction on problematic DMS backfill. From the perspective of geotechnical engineering practice, the work offers important implications by stating that adequate design optimization complemented by geosynthetic reinforced structure is an efficient way to solve those stability problems induced by weak foundation soil. This research helps promote the sustainable practice of construction through proposing a feasible way of using dredged materials in a retaining structure with economic benefit and enhanced engineering performance.